2022
DOI: 10.1017/asr.2021.147
|View full text |Cite
|
Sign up to set email alerts
|

Dancehall City: Zongo Identity and Jamaican Rude Performance in Ghanaian Popular Culture

Abstract: The explosion of Ghanaian Reggae-Dancehall reflects the influence of Jamaican-inspired popular culture in Ghana today. This subculture is championed by local Rastafarians and by youth from the zongos (internal migrant, largely Islamic, unplanned neighborhoods). Suffering social alienation, many zongo artists have adopted postures similar to their Jamaican counterparts—mirroring Rasta and rude identities as counter-hegemonic resistance. Alleyne explores several artists variously located between the zongo, the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Alleyne (1988) indicated that the Maroons believed that Accompong was God of Heaven, creator of all things, and the deity of goodness. They neither worshiped nor offered sacrifices to him.…”
Section: Maroons’ Insurrections Against the British Enslaversmentioning
confidence: 99%
See 4 more Smart Citations
“…Alleyne (1988) indicated that the Maroons believed that Accompong was God of Heaven, creator of all things, and the deity of goodness. They neither worshiped nor offered sacrifices to him.…”
Section: Maroons’ Insurrections Against the British Enslaversmentioning
confidence: 99%
“…The Caribbean Region: A Focus on Jamaica Alleyne (1988) indicated that Africans were transported by the Portuguese, the Spanish, and the British to Jamaica during the periods 1498 to 1655; from 1670 to 1808, and from 1841 to 1865 because of these European enslavers' total dependence on enslaved Africans' labor on the expanding Jamaican sugar plantations. Sierra Leone accounted for about 6%, Senegambia 6%, and South East Africa, 4.3% of Africans transported to Jamaica (Gomez, 2020).…”
Section: Traditional African Spirituality (Vodun) and The Haitian Rev...mentioning
confidence: 99%
See 3 more Smart Citations